A 3D Printed Surgical Analogue to Reduce Donor Tooth Trauma during Autotransplantation. (December 2017) - Cousley, Richard R. J.; Gibbons, Andrew; Nayler, Jeremy
Surgical trauma and prolonged extra-alveolar exposure of the donor tooth's root sheath are both complicating factors during tooth autotransplantation surgery. This case report describes a 12-year-old female patient who underwent surgical transplantation of a maxillary second premolar to a central incisor site. A three-dimensional printed analogue of the donor tooth was fabricated from a cone beam (CBCT) scan of the tooth in order to minimise the extra-oral (exposure) time and frequency of trial insertions of the donor tooth into the recipient socket. The laboratory and clinical aspects of this novel technique are described.